The Beginning of the Resistance to Milei’s Government - Rebón, Julián (2024)
At the end of 2023, Javier Milei assumed the presidency of the Republic of Argentina, presenting himself as the first libertarian president in history. In his inaugural address, he spoke to his assembled supporters, with his back to Congress and the members of parliament in attendance. He promised to put an end to Argentina’s decadence by introducing adjustments to the state and the “caste”: a vague term referring to supposedly privileged political figures ranging from traditional politicians to trade unionists and public employees. Those present responded to him from the square with jubilant chants of “no hay plata” (there is no money)...